Innovation, Practice, and Adaptation to Climate in the Aquaculture Sector. Issue 4 (2nd October 2021) - Lebel, Louis; Navy, Hap; Jutagate, Tuantong; Akester, Michael Joseph; Sturm, Lenore; Lebel, Phimphakan; Lebel, Boripat
Abstract: The importance of innovation for effective responses to climate change is widely asserted, but exactly how and whom innovation helps adapt has received little systematic attention. In this synthetic review, a practice-oriented framework is used to show that innovations which contribute to adaptation in the aquaculture sector include changes to the material, procedural and informational dimensions of practice. The material dimension is dominated by concerns with cost and competitiveness, whereas for the procedural dimension issues of skills and compliance arise, and for the informational dimension, key issues are trust, reliability and persuasiveness. A secondary classification into ten types of practices identified additional associations with adaptation mechanisms, for instance, technical practices are followed and adjusted to reduce and manage risks, while many infrastructural and technological practices aim to control rearing environments. Innovation has been driven more by concerns with increasing productivity, disease control, and food safety than extreme weather events and climate change. Nevertheless, many new practices have significant implications for adaptation. This study also shows that innovation and adaptation are timebound and face social limits, and these are better understood when different dimensions and types of practice, sources of innovation, and mechanisms of adaptation are distinguished.